2015
DOI: 10.4209/aaqr.2015.05.0300
|View full text |Cite
|
Sign up to set email alerts
|

Use of Spinel Nickel Aluminium Ferrite as Self-Supported Oxygen Carrier for Chemical Looping Hydrogen Generation Process

Abstract: Chemical looping hydrogen generation (CLHG), as a new technology involved in chemical looping combustion (CLC) process and steam-iron process, has attracted attention for clean energy generation and efficient energy conversion. A systematic investigation of spinel NiFeAlO 4 has led to characterization of a well-defined self-supported oxygen carrier which was prepared by solid state reaction. The redox behavior of NiFeAlO 4 shows the enhancement on the resistance to agglomeration exceeding previously reported C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Interestingly, the NiFe 2 O 4 particles on Al 2 O 3 ‐1200 are no longer evident after TGA. In accordance with previous studies, we speculated that the NiFe 2 O 4 particles are incorporated into the framework of the Al 2 O 3 ‐1200 to form a solid solution. Then the shell and macropores formed through this interaction at the extremely high temperature.…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, the NiFe 2 O 4 particles on Al 2 O 3 ‐1200 are no longer evident after TGA. In accordance with previous studies, we speculated that the NiFe 2 O 4 particles are incorporated into the framework of the Al 2 O 3 ‐1200 to form a solid solution. Then the shell and macropores formed through this interaction at the extremely high temperature.…”
Section: Resultssupporting
confidence: 90%
“…Zhou et al (2014) demonstrated that high CO 2 selectivity and CH 4 conversion for CLC operated in the batch fluidized bed reactor with NiO, and also reported that the operation time of approximately 6 min was achieved for 95% of NiO conversion by CLC operated in the fixed bed reactor, while the operation time of 95% of NiO conversion by CLC operated in the fluidized bed reactor reached lower than 3 min, indicating that the longer reaction times of the gas inside the reactor lead to faster conversions of the oxygen carrier. Wang et al (2016) studied that the kinetic study of Mn-based oxygen carrier for oxygen release by chemical looping air separation (CLAS), and also reported that the first-order chemical reaction model (C1) and Avrami-Erofe'ev random nucleation and subsequence growth model (A2) Kuo et al (2015) reported that the spinel structure of NiFeAlO 4 oxygen carriers presented high CO conversion and H 2 generation has been proved in fixed bed reactor for chemical looping hydrogen generation process (CLHG), because the ability of self-supported and agglomeration resistance were significantly enhanced. Chiu and Ku (2012) reported that the gasification of solid fuel in the fuel reactor is the rate limiting step for direct solid fuel combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Ku et al (2014) revealed that the completely methane combustion was achieved for experiments carrier out with Fe 2 O 3 /Al 2 O 3 in a moving bed fuel reactor, and carbon deposition was significantly reduced. Kuo et al (2015) reported that the high H 2 generation for chemical looping hydrogen generation process (CLHG) with NiFeAlO 4 oxygen carriers was contributed to the spinel structure of NiFeAlO 4 .…”
Section: Introductionmentioning
confidence: 99%